Managing Agricultural Development in Nigeria : proceedings of the inaugural seminar of the Agricultural and rural management training institute, Ilorin, Nigeria held at ASCON, Badagry in July 1981 - Ijere M. O.; Idachaba, F. C. (Ilorin : Agricultural and Rural Management Training Institute, 1983)
This book is a seminar held at Administrative Staff College of Nigeria, Badagry. The seminar examines the factors responsible for the failure of many government and non-government projects in Nigeria and why.
Includes bibliographical references
hza 13/02/2019
Loans
Keywords: Agriculture; Nigeria